DECISION MAKING AND ADAPTATION PROCESSES TO CLIMATE CHANGE - BUSTOS,EDUARDO SANDOVAL (2016)
Abstract Climate change imposes certain challenges not only to ecosystems but to societies as well. The change in environmental conditions makes necessary to review the decision-making process related to adaptation to climate change. This review should consider future risks or current conditions of vulnerability through existing mechanisms in organizations or societies. From this analysis onwards, processes must be developed allowing, either to prepare the way to face expected future impacts or to decrease the current vulnerability regarding climate by creating more resilient systems. In this context, the role of the academy, as a knowledge source, results fundamentally. Nevertheless, this highlight the need to review and improve the communication processes from academy towards different interests groups by means of the co-production and strengthening of links among different society components.